Microwave-Assisted Rapid Synthesis of 166Ho-1,4,7,10-Tetraazacyclododecane-N,N',N'',N'''- Tetraacetic Acid:A Bifunctional Chelating Agent for Radiopharmaceuticals - HYUN PARK, SANG; JEONG GWON, HUI; HO JANG, SEUNG (Asian Journal of Chemistry, 2010)
A rapid procedure for the preparation of 166Ho-1,4,7,10-tetraazacyclododecane-N,N',N'',N'''-tetraacetic acid (DOTA), a bifunctional chelating, agent for therapeutic radiopharmaceuticals, was established. The [166Ho(DOTA)]- chelate was prepared in very short reaction times (0.5-1 min) with good yields (99%) under microwave irradiation (300 W), while it was prepared at elevated temperatures over 3 h in the conventional method. The microwave irradiation offers a rapid and efficient methodology for the formation of the 166Ho-complex.